Glutamate-related gene expression changes with age in the mouse auditory midbrain - Tadros, Sherif F.; D'Souza, Mary; Zettel, Martha L.; Zhu, XiaoXia; Waxmonsky, Nicole C.; Frisina, Robert D. (Brain research, 2007)
Glutamate is the main excitatory neurotransmitter in both the peripheral and central auditory systems. Changes of glutamate and glutamate-related genes with age may be an important factor in the pathogenesis of age-related hearing loss—presbycusis. In this study, changes in glutamate-related mRNA gene expression in the CBA mouse inferior colliculus with age and hearing loss were examined and correlations were sought between these changes and functional hearing measures, such as the auditory brainstem response (ABR) and distortion product otoacoustic emissions (DPOAEs). Gene expression of 68 glutamate-related genes was investigated using both genechip microarray and real-time PCR (qPCR) molecular techniques for four different age/hearing loss CBA mouse subject groups. Two genes showed consistent differences between groups for both the genechip and qPCR. Pyrroline-5-carboxylate synthetase enzyme ( Pycs) showed down-regulation with age and a high-affinity glutamate transporter ( Slc1a3) showed up-regulation with age and hearing loss. Since Pycs plays a role in converting glutamate to proline, its deficiency in old age may lead to both glutamate increases and proline deficiencies in the auditory midbrain, playing a role in the subsequent inducement of glutamate toxicity and loss of proline neuroprotective effects. The up-regulation of Slc1a3 gene expression may reflect a cellular compensatory mechanism to protect against age-related glutamate or calcium excitoxicity.